Plug-in for Annotating Semantic Effect on BPMN Business Process Models - Hadi, Hilman Nuril; Kurniawan, Tri Astoto; Aknuranda, Ismiarta (Journal of Information Technology and Computer Science, 2019)
BPMN has become the standard of business process modeling indescribing the existing series of business process. By engaging BPMN, an analystwould possibly able to model the whole business process activities in whichhe/she may analyze business process upon design time. It can be done byanalyzing the structure, behavior, or semantic of process model. In certaincondition one may ask a question what would the effects of the process be if itwere to be executed up to this point?. However, it cannot be solved with onlygraphical notation, but with its semantics. In practice, several modeling tools stilldo not provide a feature for managing information regarding the effects/resultsin the business process model. In fact, analysts should be supported with a toolin order to semantically enrich a process model with its effects. This articledescribes effect annotation semantically towards activity in the BPMN modelincluding the rules in representing its effects. The effect annotation will be suitedtowards activity type (atomic and compound activities). The outcomes of plugin development of eclipse BPMN2 modeler for representing semantic effect arealso described in this paper.